Penerapan Metode Topsis dalam Penentuan Pengadaan Judul Buku di Perpustakaan - Rajib Ghaniy; Reyhan Dwi Putra (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Procurement of books is one of the jobs of a librarian, both in university libraries and public libraries, the procurement of books itself has several stages and one of them is determining the priority books to be purchased first and also recommendations for additional or other supporting books. In one of the business college libraries in the city of Bogor, there are still obstacles in determining the title of the book to be purchased due to the workings and the assessment process which is still done manually and repeatedly, therefore in this study, an application was made that can determine the title. Books that can be prioritized to be purchased first and also other alternatives in the form of a ranking system that uses the title of the book as an alternative and also some special criteria used that have been approved by the relevant library such as the year of publication, the availability of complete books, and also book reviews. This research was conducted to make it easier for library staff and also to increase the effectiveness of determining the priority book titles in one application count. And also a feasibility test has been carried out on the application made, with a feasibility value of 85%, which means the application made is very feasible and has also been tested for accuracy using the formula confusion matrix with an accuracy value of 100%.